2019
DOI: 10.12659/msm.912912
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wrist Arthroscopy, Small Incision Surgery, and Conventional Surgery for the Treatment of Carpal Tunnel Syndrome: A Retrospective Study at a Single Center

Abstract: Background This study aimed to compare the efficacy and safety of wrist arthroscopy, small incision surgery, and conventional open carpal tunnel release surgery for the treatment of carpal tunnel syndrome. Material/Methods Patients with carpal tunnel syndrome (n=111) were treated with wrist arthroscopy (n=33), small incision surgery (n=40), and conventional open carpal tunnel release surgery (n=38). Incision length, duration of surgery, degree of intraoperative bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…In terms of clinical effects, the treatment group after treatment had a remarkably higher cure rate than the control group ( P < 0.05), probably because acupotomy reduced the compression on median nerve in the carpal tunnel by cutting and loosening the transverse carpal ligament, addressing the cause of the disease at its source [ 21 ]. Some scholars believe that [ 22 , 23 ] the acupotomy treatment of CTS improves blood circulation, accelerates metabolism, and better repairs muscle ligament injury. Electroacupuncture promotes the repair of median nerve and the recovery of wrist function and can also dredge local meridian qi [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical effects, the treatment group after treatment had a remarkably higher cure rate than the control group ( P < 0.05), probably because acupotomy reduced the compression on median nerve in the carpal tunnel by cutting and loosening the transverse carpal ligament, addressing the cause of the disease at its source [ 21 ]. Some scholars believe that [ 22 , 23 ] the acupotomy treatment of CTS improves blood circulation, accelerates metabolism, and better repairs muscle ligament injury. Electroacupuncture promotes the repair of median nerve and the recovery of wrist function and can also dredge local meridian qi [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were multiple kinds of mini-incision approaches or novel instruments for CTR surgery [4,6,12,[14][15][16][17][18][19]. The assisted endoscopic technique was one among firstly used techniques, but was limited in wide use for high cost for purchase and maintenance, and the relatively higher rate of iatrogenic injury to vital structures [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our minimal invasive technique using mini-bush hook can be an alternative to the endoscopic technique for CTR. As an early minimally invasive technique, endoscopic CTR has advantage in significantly reducing surgical site-related complications, but is limited to widespread use due to high cost of equipment and setup and need for a steep learning curve, increased risk of iatrogenic injury to nerve or blood vessel and occasionally the incomplete release [ 6 , 9 , 13 ]. In contrast, our minimally invasive technique is promising in widespread use for second- or primary-level medical institutions where endoscopic equipment was not affordable or not readily available, due to the very low cost, simple and easy operation to perform, hardly need of specific learning and more importantly the similar clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts for minimally invasive surgery have been introduced into practice for treatment of CTS, including endoscopic carpal tunnel release (ECTR) and various kinds of small incision surgery (mid- or root-palmar longitudinal incision, wrist palmar transverse incision) [ 6 , 8 ]. These methods each had their own advantages or disadvantages; however, no one method is absolutely superior to the other one [ 9 ]. Furthermore, most of them were small-sample pilot study, and the reported clinical results have hardly been validated.…”
Section: Introductionmentioning
confidence: 99%